Clinician-Patient Discord: Exploring Differences in Perspectives for Discontinuing Clopidogrel - Garavalia, Linda (2010)
BACKGROUND: Premature stopping of anti-platelet therapy has potentially fatal consequences for myocardial infarction (MI) patients who have received a drug eluting stent (DES). Exploring multiple perspectives to identify contributing factors to the problem is essential. AIM: We gained patient and clinician perspectives as to why MI patients prematurely stop anti-platelet therapy (clopidogrel) after DES implantation. METHODS: This qualitative, descriptive study of DES-treated MI patients (n=22) and of clinicians (physicians and nurse practitioners; n=17) from multiple U.S. cities used content analysis of interview data. Findings across patients and clinicians were then compared to examine congruent and contrasting reasons for premature clopidogrel discontinuance. FINDINGS: Patients frequently identified communication and education (e.g. unaware they should be taking clopidogrel, unaware of intended duration of therapy) as the primary reasons for having stopped. Patients rarely cited cost, while clinicians most commonly cited cost as a reason for premature stopping. CONCLUSIONS: The discrepancy in perceptions of patients and clinicians as to the primary reason for early discontinuance suggests an important opportunity for improving persistence. Rather than focusing on the high costs of medications, something outside of their control, physicians should consider communicating more effectively the importance and intended duration of clopidogrel to their patients.